2013
DOI: 10.1371/journal.pone.0054271
|View full text |Cite
|
Sign up to set email alerts
|

Type-1 (CB1) Cannabinoid Receptor Promotes Neuronal Differentiation and Maturation of Neural Stem Cells

Abstract: Neural stem cells (NSCs) are self-renewing cells that can differentiate into multiple neural lineages and repopulate regions of the brain after injury. We have investigated the role of endocannabinoids (eCBs), endogenous cues that modulate neuronal functions including neurogenesis, and their receptors CB1 and CB2 in mouse NSCs. Real-time PCR and Western blot analyses indicated that CB1 is present at higher levels than CB2 in NSCs. The eCB anandamide (AEA) or the CB1-specific agonist ACEA enhanced NSC different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 56 publications
(92 reference statements)
9
76
0
Order By: Relevance
“…Moreover, the authors reported in their previous results that ACEA alone and in combination with another antiepileptic drug valproate significantly increased neurogenesis in healthy and PILO mice [32,38]. Similar results were obtained by Compagnucci and et al [31], where the endocannabinoid anandamide (AEA) as well as ACEA enhanced NSC differentiation into neurons, whereas the CB 2 -specific agonist JWH133 was ineffective. Investigations with mouse PILO model of epilepsy allowed the observation and evaluation of the neurogenesis changes in the epileptic mouse brain.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, the authors reported in their previous results that ACEA alone and in combination with another antiepileptic drug valproate significantly increased neurogenesis in healthy and PILO mice [32,38]. Similar results were obtained by Compagnucci and et al [31], where the endocannabinoid anandamide (AEA) as well as ACEA enhanced NSC differentiation into neurons, whereas the CB 2 -specific agonist JWH133 was ineffective. Investigations with mouse PILO model of epilepsy allowed the observation and evaluation of the neurogenesis changes in the epileptic mouse brain.…”
Section: Discussionsupporting
confidence: 74%
“…However, interestingly, administration during adolescence decreased the number of immature neurons, an affect that is attributed to selective suppression of dorsal but not ventral hippocampal neurogenesis [30]. The endocannabinoid anandamide (AEA) or the CB1-specific agonist ACEA displayed a higher degree of neural stem cells neuronal differentiation and maturation in vitro, and enhanced neuronal stem cells differentiation into neurons, but not astrocytes and oligodendrocytes [31].…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained by Rivera et al (2015) showed that repeated treatment with another cannabinoid URB597 (fatty acid amide hydrolase inhibitor), decreases neural proliferation, glia and apoptosis in the rat hippocampus, whereas acute URB597 treatment showed an increased number of subventricular proliferative, astroglial and apoptotic cells. The endocannabinoid anandamide (AEA) or the CB1-specific agonist ACEA displayed a high degree of neural stem cells differentiation and maturation into neurons, but not astrocytes and oligodendrocytes (Compagnucci et al, 2013). Avraham and coworkers (2014a) found that the cannabinoid CB2-receptor agonist AM1241 enhances neurogenesis in GFAP/Gp120 transgenic mice displaying deficits in neurogenesis caused by HIV-1/Gp120 insult.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding cell fate decisions, endocannabinoids are involved in astroglial differentiation from NSPC, in a CB1-dependent manner ), but recent reports suggest that CB1 receptor activation may also enhance NPSC differentiation into neurons (Compagnucci et al 2013). However, there is limited information on the action of endocannabinoids in oligodendrocytes, the myelinating cells of CNS.…”
Section: Introductionmentioning
confidence: 99%